2018
DOI: 10.1016/j.trsl.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Unique metabolomic signature associated with hepatorenal dysfunction and mortality in cirrhosis

Abstract: The application of nontargeted metabolomic profiling has recently become a powerful noninvasive tool to discover new clinical biomarkers. This study aimed to identify metabolic pathways that could be exploited for prognostic and therapeutic purposes in hepatorenal dysfunction in cirrhosis. One hundred three subjects with cirrhosis had glomerular filtration rate (GFR) measured using iothalamate plasma clearance, and were followed until death, transplantation, or the last encounter. Concomitantly, plasma metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 73 publications
(129 reference statements)
4
52
0
1
Order By: Relevance
“…The greatest change (2.39) was for 4-acetamidobutanoate, the acetylated metabolite of GABA and a product of arginine and proline metabolism (http://www.hmdb.ca/metabolites/HMDB0003681). Pathway enrichment analysis identified glucuronidation and methylation, together with ascorbate and aldarate metabolism, that were linked to hepatorenal dysfunction [138]. Another study in China used both NMR and UPLC-ESI-QTOFMS to analyze serum from LC (42), HCC (43) and HV (18).…”
Section: Fibrosis and Cirrhosismentioning
confidence: 99%
“…The greatest change (2.39) was for 4-acetamidobutanoate, the acetylated metabolite of GABA and a product of arginine and proline metabolism (http://www.hmdb.ca/metabolites/HMDB0003681). Pathway enrichment analysis identified glucuronidation and methylation, together with ascorbate and aldarate metabolism, that were linked to hepatorenal dysfunction [138]. Another study in China used both NMR and UPLC-ESI-QTOFMS to analyze serum from LC (42), HCC (43) and HV (18).…”
Section: Fibrosis and Cirrhosismentioning
confidence: 99%
“…A unique metabolomic signature consisting of 34 metabolites that significantly increased in patients with high liver and kidney disease severity has recently been described in patients with cirrhosis [18]. Among these metabolites, 4-acetamidobutanoate, trans-aconitate, 1-methylhistidine, glucuronate, N4-acetylcytidine, 3-ureidopropionate, 3-methoxytyramine sulfate, cytidine, S -adenosylhomocysteine (SAH) and myo-inositol were the 10 most significantly increased ones when patients with high liver and kidney liver disease severity were compared with those with low liver and kidney disease severity [18].…”
Section: Current Applications Of Metabolomics In Cirrhosismentioning
confidence: 99%
“…A unique metabolomic signature consisting of 34 metabolites that significantly increased in patients with high liver and kidney disease severity has recently been described in patients with cirrhosis [18]. Among these metabolites, 4-acetamidobutanoate, trans-aconitate, 1-methylhistidine, glucuronate, N4-acetylcytidine, 3-ureidopropionate, 3-methoxytyramine sulfate, cytidine, S -adenosylhomocysteine (SAH) and myo-inositol were the 10 most significantly increased ones when patients with high liver and kidney liver disease severity were compared with those with low liver and kidney disease severity [18]. This study that used ultrahigh performance liquid chromatography/tandem mass spectrometry to detect plasma metabolites, also showed that all signature metabolites were independent predictors of glomerular filtration rate measured by non-radiolabeled iothalamate plasma clearance in patients with cirrhosis; and erythronate had the highest significant association with measured glomerular filtration rate [18].…”
Section: Current Applications Of Metabolomics In Cirrhosismentioning
confidence: 99%
“…The latter hypothesis was recently reinforced by the discovery of a biosignature of plasma metabolites that correlated with hepatorenal dysfunction in patients with cirrhosis. 6 Patients with ACLF-3 and HRS had a considerable risk of 90-day mortality of up to 80% in this study. Does this mean that we should not treat HRS in patients with ACLF-3 at all?…”
mentioning
confidence: 53%